Dispersal restricts local biomass but promotes the recovery of metacommunities after temperature stress. Issue 6 (6th February 2014) - de Boer, M. Karin; Moor, Helen; Matthiessen, Birte; Hillebrand, Helmut; Eriksson, Britas Klemens
<x xml:space="preserve">Abstract</x> Landscape connectivity can increase the capacity of communities to maintain their function when environments change by promoting the immigration of species or populations with adapted traits. However, high immigration may also restrict fine tuning of species compositions to local environmental conditions by homogenizing the community. Here we demonstrate that dispersal generates such a tradeoff between maximizing local biomass and the capacity of model periphyton metacommunities to recover after a simulated heat wave. In non‐disturbed metacommunities, dispersal decreased the total biomass by preventing differentiation in species composition between the local patches making up the metacommunity. On the contrary, in metacommunities exposed to a realistic summer heat wave, dispersal promoted recovery by increasing the biomass of heat tolerant species in all local patches. Thus, the heat wave reorganized the species composition of the metacommunities and after an initial decrease in total biomass by 38.7%, dispersal fueled a full recovery of biomass in the restructured metacommunities. Although dispersal may decrease equilibrium biomass, our results highlight that connectivity is a key requirement for the response diversity that allows ecological communities to adapt to climate change through species sorting.